Biomechanical comparison of lateral collateral ligament reconstruction with and without additional internal bracing using a three-dimensional elbow simulator. (January 2021) - Ellwein, Alexander; Becker, Sören; Nebel, Dennis; Horstmann, Hauke; Smith, Tomas; Lill, Helmut; Pastor, Marc-Frederic
Abstract: Background: Although an additional internal bracing significantly increases stability in a repair of the lateral ulnar collateral ligament, it remains unclear whether it also does in reconstruction. Aim of this study was to implement a three-dimensional elbow simulator for testing posterolateral rotatory instability. We hypothesized that (1) reconstruction with and without internal bracing is comparable in biomechanical properties, and (2) there would be higher load-to-failure with internal bracing. Methods: Posterolateral rotatory instability was tested by imitating the lateral pivot shift test in 16 elbows. Valgus and supination torques were simultaneously increased stepwise up to 1.2 Nm. Specimens were tested at 30°, 60°, 90°, and 120° elbow flexion with an intact lateral collateral ligament complex, dissected complex, and after reconstruction with or without internal bracing. Outcome measures included joint gapping, laxity, and load to failure. Findings: With the implemented elbow simulator no significant difference was observed for gapping or laxity between both treatment groups. Comparing treatment and native ligament, gapping was reduced, especially with increased elbow flexion. Laxity was also reduced at some flexion angles. The mean load-to-failure was 8.1 ± 2.7 Nm without and 9.6 ± 3.6 Nm with internal bracing ( P  = 0.645). Interpretation: Both treatments were comparable in biomechanical properties but did not fully restore the native state. Although the additional augmentation of the LUCL reconstruction tends to increase the maximum load to failure, this difference was not statistically significant. Still, reconstruction with internal bracing seems to be a reasonable option in selected primary reconstructions. It could also be useful in revision reconstruction. Highlights: Gapping and laxity did not differ with and without internal bracing. No difference between both treatments was observed regarding load to failure. But, both treatments did not fully restore the native state. Still, internal bracing seems to be a reasonable option in selected cases. Posterolateral rotatory instability was evaluated by imitating the pivot shift test.